Enhancement of degree of deacetylation of chitin in chitosan production - Stephenie, Ak Kalut (2008)
Chitosan is made from crustacean shells by a chemical process involving demineralization, deproteinization, decolorization, and deacetylation. The process of deacetylation involves the removal of acetyl groups from the molecular chain of chitin, leaving behind a complete amino group (-NH) and chitosan versatility depends mainly on this high degree chemical reactive amino groups. The purpose of this research is to observe the parameters that can enhance the degree of deacetylation of chitosan production to the highest percentage. The observed parameters are the temperature of heating, concentration of sodium hydroxide, and the time of heating. The obtained chitin was converted into the more useful soluble chitosan by reaction with sodium hydroxide (NaOH) solution of various concentrations, then the alkaline chitin was heated in an autoclave with different time and temperature of heating which dramatically reduced the time of deacetylation. The method used to determine the degree of deacetylation of chitosan is the linear potentiometric titration. From the result, the highest degree of deacetylation can be achieved at the temperature of 1342oC, and 70% concentration of sodium hydroxide with DDA% of 98.38% and 98.79% respectively. It took only 10 minutes to also achieve highest degree of deacetylation, 89.05%. In conclusion, the increasing of temperature and concentration of sodium hydroxide will increase the degree of deacetylation of chitin. The increasing of time of heating will decrease the degree of deacetylation.